(3QhVI GdfSQjf aj OhdI Hfi eQjfs - (3GdhdjO ESeGYjd Hf GdGejQ jhSa Hf GdSdWGf GdbGFe HCeQ Gddg eMeO Hf GdQFjS, GdGMeQ GdfUQj,J (B807 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdJGQjN ef CTQa eG Hg GdEfSGf JRjf s
(3BNQgG (B:s
(3jYWi GdNQGL ddehdi GdSdWGf YKeGf GdeQjfi GfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B105(3C (B- (3U(B129(3Cs
(3hQOJ CjVkG JMJ YfhGf (B" (3GdeYQH GdeHjf YeG JVefg GdCfS GdeWQH hQhVI GdfSQjf (B" (3HQbe (B2039" (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B216 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs